Respostas

  • Usuário do Brainly
2013-10-27T22:41:17-02:00
(2x + 6) / 3
----------------- = 12
(3x - 6) / 2
pelo metodo cruzado:
12*(3x - 6)/2 = (2x + 6)/3
(36x - 72)/2 = (2x + 6)/3
pelo metodo cruzado:
3*(36x - 72) = 2*(2x + 6)
108x - 216 = 4x + 12
108x - 4x = 12 + 216
104x = 228
x = 228 / 104 (simplifique por 4)
x = 57 / 26




1 5 1
2013-10-27T23:54:55-02:00
       2 (x + 3)        
            3              = 12
       3 (x - 2)
            2
            
      2x + 6      
          3              = 12
       3x - 6 
           2
2x + 6 : 3x - 6   = 12
   3           2
2x + 6   *     2     = 12
    3         3x - 6
4x + 12  = 12
9x - 18
4x + 12 = 12 (9x - 18)
4x + 12 = 108x - 216
4x - 108x = - 216 - 12
- 104x = - 228
x = - 228 : (- 104)
x = 228
      104
x = 57
      26